2017
DOI: 10.1007/s11127-017-0458-4
|View full text |Cite
|
Sign up to set email alerts
|

More politicians, more corruption: evidence from Swedish municipalities

Abstract: In the literature on political economy and public choice, it is typically assumed that government size correlates positively with public corruption. The empirical literature, however, is inconclusive, owing to both measurement problems and endogeneity. This paper creates a corruption index based on original data from a survey covering top politicians and civil servants in all Swedish municipalities. The effect of more politicians on corruption problems is analyzed using discontinuities in the required minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 44 publications
2
11
0
3
Order By: Relevance
“…Running standard OLS-regressions with perceived corruption, tax rate and citizen satisfaction as dependent variables gives the results presented in For the control variables, several associations are as expected: rich municipalities and municipalities with well-educated citizens have lower taxes. For perceived corruption, the control variables have signs similar to those reported in Bergh et al (2017). Some of these results are in line with theoretical expectations, such as perceived corruption being slightly lower where local newspapers are present.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Running standard OLS-regressions with perceived corruption, tax rate and citizen satisfaction as dependent variables gives the results presented in For the control variables, several associations are as expected: rich municipalities and municipalities with well-educated citizens have lower taxes. For perceived corruption, the control variables have signs similar to those reported in Bergh et al (2017). Some of these results are in line with theoretical expectations, such as perceived corruption being slightly lower where local newspapers are present.…”
Section: Resultssupporting
confidence: 84%
“…Williams and Brick 2018), and the response rate was at least 50 per cent in 288 of 290 municipalities. Reassuringly, in an attempt to validate the quality of this index, Dahlström and Sundell (2013) found that answers to the questions used not only correlated significantly with answers to similar questions in the indexbased on a total of less than 1,000 respondentsused by Bergh et al (2017), but also with newspaper articles about bribery as well as legal bribery charges.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a robust negative relationship exists between the size of a country's territory and the measure of the rule of law implemented in the country (Olsson & Hansson, 2011). Larger countries generally have larger governments and more politicians, both of which are potential sources of corruption (Arvate et al, 2010;Bergh et al, 2017;Goel & Nelson, 1998;Kotera et al, 2012), and, as a result, a larger population makes the risk of bribery more likely (Mocan, 2008), which, in turn, may restrict a merit-based (or equal) access to a scientific career and research opportunities.…”
Section: Does Population Size Matter?mentioning
confidence: 99%
“…One view is that since a larger government 2003, Billger and Goel (2009), and Goel and Budak (2006). The alternative view is that an increase in government size provides more opportunity for political rent-seeking, causing the politicians and bureaucrats to become more corrupt (e.g., Rose-Ackerman 1978Alesina and Angeletos 2005, Goel and Nelson 1998, Arvate et al 2010, and Bergh et al 2017).…”
Section: Other Explanatory Variablesmentioning
confidence: 99%